The Impact of Trade Liberalization on the Trade Balance in Developing Countries - Wu, Yi (IMF Working Papers; Working Paper ;, 2008)
Using two recently constructed measures of trade liberalization dates, this research studies the impact of trade liberalization on imports, exports, and overall trade balance for a large sample of developing countries. We find strong and consistent evidence that trade liberalization leads to higher imports and exports. However, in contrast Santos-Paulino and Thirwall (2004) who find a robustly negative impact of trade liberalization on the overall trade balance, we only find mixed evidence of such a negative impact. In particular, we find little evidence of a statistically significant negative impact using our first measure of liberalization dates which extends Li (2004). Using a second measure of liberalization dates compiled by Wacziarg and Welch (2003), we find some evidence that liberalization worsens the trade balance, but the evidence is not robust across different estimation specifications, and the estimated impact is smaller than that reported by Santos-Paulino and Thirwall (2004).